1947
DOI: 10.1063/1.1746282
|View full text |Cite
|
Sign up to set email alerts
|

Length Changes of Activated Carbon Rods Caused by Adsorption of Vapors

Abstract: The length variations of two zinc chloride activated carbon rods caused by the adsorption of several vapors are reported. The relationship between percent extension of the rod and calculated spreading pressure of the adsorbed film suggested by Bangham has been tested. The relation agrees well with experiment for organic vapors above about ⅓ saturation of the monolayer capacity. It does not agree in the low adsorption region nor along the desorption branch of the water isotherm. A marked contraction of the rod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

1957
1957
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 10 publications
5
33
0
Order By: Relevance
“…This early work was followed by experimental studies of the swelling of charcoal that accompanies the adsorption of water, carbon dioxide and other gases by Bangham and Fakhoury [2] and several investigations of the extension of carbon rods under the influence of a variety of organic vapours by Canadian groups [3][4][5]. More recent experimental work on the deformation of carbons during the adsorption of different gases has been reported by Fomkin and co-workers [6][7][8] and a dilatometric investigation of the deformation of carbon xerogels has been made by Balzer and co-workers [9] who concluded that micropores in the adsorbents made the most significant contribution to the expansion and contraction of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…This early work was followed by experimental studies of the swelling of charcoal that accompanies the adsorption of water, carbon dioxide and other gases by Bangham and Fakhoury [2] and several investigations of the extension of carbon rods under the influence of a variety of organic vapours by Canadian groups [3][4][5]. More recent experimental work on the deformation of carbons during the adsorption of different gases has been reported by Fomkin and co-workers [6][7][8] and a dilatometric investigation of the deformation of carbon xerogels has been made by Balzer and co-workers [9] who concluded that micropores in the adsorbents made the most significant contribution to the expansion and contraction of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…This is known as Bangham's law, which states that the strain is proportional to the change in the surface energy of the porous material. However, some experimental data contradict this statement (Boissiere et al, 2005;Dolino et al, 1996;Haines & McIntosh, 1947;Sharifi et al, 2014). Thus, Gor and Bernstein (2016) revisited the Bangham's law.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, direct measurements of adsorptive deformation essentially are not conducted nowadays. Only measurements of structural characteristics of clay minerals [2][3][4][5][6][7][8], polymeric materials [9][10][11][12][13][14][15][16][17], carbons [1,[18][19][20][21][22][23][24][25][26], zeolites [27,28], and porous glasses [29,30] are performed. Moreover, no calculations of thermodynamic characteristics of a noninert adsorbent in the process of its deformation are performed (rare exceptions are [31,32].…”
Section: Introductionmentioning
confidence: 99%